The Theory and Practice of "Nudging": Changing Health Behaviors. (12th May 2016) - Vlaev, Ivo; King, Dominic; Dolan, Paul; Darzi, Ara
Abstract: Many of the most significant challenges in health care—such as smoking, overeating, and poor adherence to evidence‐based guidelines—will only be resolved if we can influence behavior. The traditional policy tools used when thinking about influencing behavior include legislation, regulation, and information provision. Recently, policy analysts have shown interest in policies that "nudge" people in particular directions, drawing on advances in understanding that behavior is strongly influenced in largely automatic ways by the context within which it is placed. This article considers the theoretical basis for why nudges might work and reviews the evidence in health behavior change. The evidence is structured according to the Mindspace framework for behavior change. The conclusion is that insights from behavioral economics offer powerful policy tools for influencing behavior in health care. This article provides public administration practitioners with an accessible summary of this literature, putting these insights into practical use .